Pengaruh Identitas Sosial Dan Co-Creation Terhadap Niat Berperilaku Anggota Komunitas Online VW: Efek Moderasi Nostalgia - Badri Munir Sukoco; Untung Teko TP (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
Developing relationships with customers through brand community is the recent tool for marketers for customer relationship management (CRM) program. The existence of a community, especially virtual, depends on the members’ participation as well as their recommendation to others. Previous studies indicate that members’ participation and recommendation depends on how deep is their identification toward the community. This article argues that social identification itself is not enough, unless the members engage in co-creation activities by exchanging knowledge with other members (co-consumption) and producers (co-production). Further, this article further argues that the effect of social identity on members’ co-creation and behavioral intentions will be moderated by their nostalgia proneness. We conducted survey among Volkswagen Indonesia CyberCommunity (VICC) members as one of the legendary brand in Indonesia. The results indicate that direct effect of social identity on members’ behavioral intentions is greater than indirect effect through co-creation. The moderating effect of nostalgia proneness is significant on the relationship between social identity and behavioral intentions, in which the effect is larger when members’ identification is low. Managerial and academic implications are further discussed in this paper.